That Mr. Alzheimer ... you never know what he's up to, but what about me?: A discourse analysis of how Swedish spouse cargivers can make their subject positions understandable and meaningful - Lovenmark, Annica; Meranius, Martina Summer; Marmstål Hammar, Lena (International journal of qualitative studies on health and well-being, 2018)
The spouses of people suffering from dementia are commonly first-in-line caregivers. This can have a considerable effect on their own lives, health and marriages. Several studies have focused on spouses' experiences, but very few have focused in any depth on their descriptions of themselves as subjects. Therefore, the aim of this study is to describe how spouse caregivers can express themselves when living with and caring for their partners with dementia. The study has a qualitative approach with a discourse analysis design and uses analytical tools such as rhetoric, subject positions and categorization. The results reveal three subject positions: as an actor, as a parent and as a survivor. The results show that as spouses struggle with external and internal clashes as subjects, they therefore need to develop coping strategies. They also experience pronounced loneliness and a risk to their own health. There is thus a need to support these spouses as individuals in their differing and changing needs.